Relationship between Contact Inhibition and Intranuclear S100c of Normal Human Fibroblasts - Sakaguchi, Masakiyo (The Rockefeller University Press, 2000)
Many lines of evidence indicate that neoplastic transformation of cells occurs by a multistep process. For neoplastic transformation of normal human cells, they must be first immortalized and then be converted into neoplastic cells. It is well known that the immortalization is a critical step for the neoplastic transformation of cells and that the immortal phenotype is recessive. Thus, we investigated proteins downregulated in immortalized cells by two-dimensional gel electrophoresis. As a result, S100C, a Ca(2+)-binding protein, was dramatically downregulated in immortalized human fibroblasts compared with their normal counterparts. When the cells reached confluence, S100C was phosphorylated on threonine 10. Then the phosphorylated S100C moved to and accumulated in the nuclei of normal cells, whereas in immortalized cells it was not phosphorylated and remained in the cytoplasm. Microinjection of the anti-S100C antibody into normal confluent quiescent cells induced DNA synthesis. Furthermore, when exogenous S100C was compelled to localize in the nuclei of HeLa cells, their DNA synthesis was remarkably inhibited with increase in cyclin-dependent kinase inhibitors such as p16(Ink4a) and p21(Waf1). These data indicate the possible involvement of nuclear S100C in the contact inhibition of cell growth.